Konstruksi Regulasi Sistem Pemilihan Kepala Daerah Menuju Sistem Pemilihan Kepala Daerah yang Demokratis dan Aspiratif - Sulardi, Sulardi; Sulistyaningsih, Tri (Jurnal Media Hukum, 2017)
This research is expected to produce the formulation of regulations on the regional election democratic and aspirational in order to embody democracy and good governance, from centralist to decentralization, of authoritarian to democracy. This research approah is a constructivism paradigm. The characteristics of this research are: first, this research uses an approach which law that manage the election as a mental construction reality of individual result of writing, and subjective action. Second, to get the data, the writer interact with expertises accurately and also governmental parties who are competent in this focus of research. Third, the interaction between the writer and expertises is conducted directly. Fourth, in accordance to various scientific literature works, then used as guidance by the researcher to conduct their own regulation construction in regional election. Fifth, conducting focus group dicsussion to get input for the improvement of this research.